Machine learning and systems engineering - Ao, Sio-Iong.; Rieger, Burghard B.; Amouzegar, Mahyar A. (Dordrecht ; New York : Springer, 2010)
"A large international conference on Advances in Machine Learning and Systems Engineering was held in UC Berkeley, California, USA, October 20-22, 2009, under the auspices of the World Congress on Engineering and Computer Science (WCECS 2009). Machine Learning and Systems Engineering contains forty-six revised and extended research articles written by prominent researchers participating in the conference. Topics covered include Expert system, Intelligent decision making, Knowledge-based systems, Knowledge extraction, Data analysis tools, Computational biology, Optimization algorithms, Experiment designs, Complex system identification, Computational modeling, and industrial applications. Machine Learning and Systems Engineering offers the state of the art of tremendous advances in machine learning and systems engineering and also serves as an excellent reference text for researchers and graduate students, working on machine learning and systems engineering."--Publishers description
Multimodal Human Spacecraft Interaction in Remote Environments -- A Framework for Collaborative Aspects of Intelligent -- Piecewise Bezier Curves Path Planning with Continuous Curvature Constraint for Autonomous -- Combined Heuristic Approach to Resource-Constrained Project -- A Development of Data-Logger for Indoor Environment -- Multiobjective Evolutionary Optimization and Machine Learning : Application to Renewable Energy Predictions -- Hybriding Intelligent Host-Based and Network-Based Stepping Stone Detections -- Open Source Software Use in City Government -- Pheromone-Balance Driven Ant Colony Optimization with Greedy Mechanism -- Study of Pitchfork Bifurcation in Discrete Hopfield Neural -- Grammatical Evolution and STE Criterion -- Data Quality in ANFIS Based Soft Sensors -- The Meccano Method for Automatic Volume Parametrization of Solids -- A Buck Converter Model for Multi-Domain --The Computer Simulation of Shaping in Rotating Electrical Discharge -- Parameter Identification of a Nonlinear Two Mass System -- Adaptive and Neural Learning for Biped Robot Actuator Control -- Modeling, Simulation, and Analysis for Battery Electric Vehicles -- Modeling Confined Jets with Particles and Swril -- Robust Tracking and Control of Mimo Processes with Input Saturation and Unknown Disturbance -- Analysis of Priority Rule-Based Scheduling in Dual-Resource-Constrained Shop-Floor -- A Hybrid Framework for Servo-Actuated Systems Fault Diagnosis -- Multigrid Finite Volume Method for FGF-2 Transport and Binding -- Integrated Mining Fuzzy Association Rules For Mineral Processing State Identification -- A Combined Cycle Power Plant Simulator: A Powerful, Competitive, and Useful Tool for Operator's Training -- Texture Features Extraction in Mammograms Using Non-Shannon Entropies -- A Wideband DOA Estimation Method Based on Arbitrary Group Delay -- Spatial Speaker Spatial Positioning of Synthesized Speech in Java -- Commercial Break Detection and Content Based Cideo Retrieval -- ClusterDAM: Clustering Mechanism for Delivery of Adaptive Multimedia Content in Two-Hop Wireless Networks -- Ranking Intervals in Complex Stochastic Boolean Systems Using Intrinsic Ordering -- Predicting Memory Phases -- Information Security Enhancement to Public-Key Cryptosystem Through Magic Squares -- Resource Allocation for Grid Applications : An Economy Model -- A Free and Didactic Implementation of the Send Protocol for Ipv6 -- A Survey of Network Benchmark Tools -- Hybrid Stock Investment Strategy Decision Support System -- Towards Performance Analysis of Ad hoc Multimedia Network -- Towards the Performance Optimization of Public-Kkey Algorithms Using Fuzzy Modular Arithematic and Addition Chain -- RBDT-1 Method : Combining Rules and Decision Tree Capabilities -- Computational and Theoretical Concepts for Regulating Stem Cells Using Viral and Physical Methods -- DFA, a Biomedical Checking Tool for the Heart Control System -- Generalizations in Mathematical Epidemiology -- Review of Daily Physical Activity Monitoring System Based on Single Triaxial Accelerometer and Portable Data Measurement Unit -- A Study of the Protein Folding Problem by a Simulation Model -- Analysing Multiobjective Fitness Function with Finite State Automata.
computer bookfair2016
Includes bibliographical references and index.
Keywords: Machine learning; Systems engineering